2005
DOI: 10.1136/bjsm.2004.011650
|View full text |Cite
|
Sign up to set email alerts
|

Does changing the configuration of a motor racing circuit make it safer?

Abstract: Objectives: To assess the pattern of injuries presenting to a racing circuit medical centre in two three-year periods before and after two chicanes were built into the track. Methods: Medical centre records were used to identify all patients assessed during the two time periods. Those referred to hospital were categorised by injury severity into three groups. Results: The proportions of those attending the medical centre that were referred and admitted to hospital were the same in both periods (12-13% and 3% r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 2 publications
(3 reference statements)
0
6
0
1
Order By: Relevance
“…This change has not only enraged fans and drivers alike, but is extremely inconsistent. It has been demonstrated that chicanes are not really effective in improving the safety of a racing circuit, since they reduce the risk of injury for car drivers only slightly and are mostly unsuccessful in preventing motorcycling accidents 12. Therefore, since the redesign and deformation of traditional circuits is costly and potentially unproductive, driver safety may be improved by alternative measures that will not substantially affect the attractiveness of motor racing.…”
Section: Perspectivesmentioning
confidence: 99%
“…This change has not only enraged fans and drivers alike, but is extremely inconsistent. It has been demonstrated that chicanes are not really effective in improving the safety of a racing circuit, since they reduce the risk of injury for car drivers only slightly and are mostly unsuccessful in preventing motorcycling accidents 12. Therefore, since the redesign and deformation of traditional circuits is costly and potentially unproductive, driver safety may be improved by alternative measures that will not substantially affect the attractiveness of motor racing.…”
Section: Perspectivesmentioning
confidence: 99%
“…The 125-cc class uses a 2-stroke engine while Moto2 and MotoGP use 4-stroke engines. Although road-race motorcycling performance depends on the characteristics of the motorcycle as well as on the capabilities of the riders, research has focused mainly on the technology advances of the motorbikes and riding equipment [8,23] , pattern of injuries [16,28,29] , and safety [20,21] . At the present, there are few scientifi c data on the physical and physiological load in training and competition [2,6,7,10,13] , and there is no information on the anthropometric and physical characteristics of road-race motorcyclists.…”
Section: Introduction ▼mentioning
confidence: 99%
“…4 Technical advances in racing car construction as well as changes in track layout have considerably reduced the risk of accidents and serious injury. 5 Direct trauma and other lifethreatening injuries are rarely seen, but as racing cars have become increasingly rigid, there is still a high incidence of concussion. 6 Direct trauma mainly affects the head, neck, and legs of racing drivers.…”
mentioning
confidence: 99%